Případ The Freedom Bus: Analýza výpovědí playback divadelníků o komunitní práci v kontextu izraelsko-palestinského konfliktu - Nýdrlová, Veronika (Lidé města, 2024)
This article deals with the specific project called The Freedom Bus, whose participants help those living in the Palestinian Territories in their unfavourable life situation. Namely, we discuss the project from March 2016. Playback Theatre, a method of applied drama, represents one of the means of reflecting the experience of life under occupation. The important themes that four interviews with people engaged in the project manifest are then summarised by the interpretation of data in second part of the article.